PENERAPAN MEDIA TANAM LIMBAH BAGLOG JAMUR TIRAM DAN KOMPOS BIOCHAR TERHADAP TANAMAN PAKCOY - Bria, Deseriana; Naisali, Hyldegardis; Tobing, Wilda Lumban; Ndua, Natalia Desy Djata; Mali, Dementrius Dedi (Agriculture Faculty of Flores University, 2025)
Pakcoy cultivation in horticultura, organic material in the form of waste such as white oyster mushroom baglog waste. Baglog waste compost contains 2.03% N, 0.61% P and 1.78% K, this nutrient content is able to meet the nutrient needs of plants. Another organic material that can be used as a planting medium is biochar compost. Biochar compost can increase plant growth and yield. The aim of this research was to determine the comparative effect of white oyster mushroom baglog waste and biochar compost as a planting medium on the growth and yield of pak choy plants. The research used a randomized factorial design. White oyster mushroom baglog waste is the factor I have of three levels: baglog waste 0.625 kg/polybag (L1), baglog waste 1.25 kg/polybag (L2), baglog waste 1.875 kg/polybag (L3). Biochar compost is the second factor have of three levels: 0.625 kg biochar compost/polybag (B1), 1.25 kg biochar compost/polybag (B2), 1.875 kg biochar compost/polybag (B3). Each treatment was repeated 3 times so that there were 27 experimental units. The results of the was an interaction between white oyster mushroom baglog waste and biochar compost on the parameters of plant height 14-35 DAP, number of leaves 14-35 DAP, root dry weight, shoot dry weight with the best treatment of baglog waste 0.625 kg/polybag and biochar compost 0.625 kg/polybag. Providing white oyster mushroom baglog waste fertilizer had a significant effect on all observation parameters with the best treatment being baglog waste 0.625 kg/polybag.